2022
DOI: 10.1037/apl0000882
|View full text |Cite
|
Sign up to set email alerts
|

Pain or gain? Understanding how trait empathy impacts leader effectiveness following the provision of negative feedback.

Abstract: Although providing negative performance feedback can enhance employee performance, leaders are sometimes reluctant to engage in this activity. Reflecting this, prior research has identified negative feedback provision as an aversive, yet potentially rewarding, managerial activity. However, little is known about how providing negative feedback impacts the effectiveness of leaders who do so. To shed light on this issue, we develop and test a theoretical model that identifies how leaders' proximal and distal reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 98 publications
2
10
0
Order By: Relevance
“…Supervisors and their subordinates had to complete daily surveys over a period of 2 weeks (10 consecutive days, Monday to Friday). Actually, the sample size of this study is comparable to other ESM studies recently published in top-tier journals (e.g., Lanaj et al (2021) , within-person level = 645, between-personal level = 80; Simon et al (2022) , within-person level = 422, between-personal level = 53). Future studies could anticipate the required sample size by power analyses before conducting ESM studies.…”
Section: Discussionsupporting
confidence: 72%
“…Supervisors and their subordinates had to complete daily surveys over a period of 2 weeks (10 consecutive days, Monday to Friday). Actually, the sample size of this study is comparable to other ESM studies recently published in top-tier journals (e.g., Lanaj et al (2021) , within-person level = 645, between-personal level = 80; Simon et al (2022) , within-person level = 422, between-personal level = 53). Future studies could anticipate the required sample size by power analyses before conducting ESM studies.…”
Section: Discussionsupporting
confidence: 72%
“…Participants were asked to write as detailed description of what happened as possible; to craft their responses so that someone reading them “might feel what you felt from learning about your experience”; and to “try to relive the experience as you write, pretending you are actually there and remembering how you felt during the experience and the details of the scene” (e.g., Oc et al, 2020; Simon et al, 2022). Given that directing participants to remember specific details of an event facilitates recall (Robinson & Clore, 2001), we prompted participants to write as much as possible, quoting their partner’s words and behaviors.…”
Section: Study 1: Methodsmentioning
confidence: 99%
“…Similarly, we assigned leaders’ results narratives valence scores to represent whether the outcomes of the situation were positive or negative. We did so because conceptualizations of situational outcomes in terms of positive and negative valence are common in psychology (see, e.g., Vroom, 1964) and because existing measures of leadership effectiveness in particular often reduce effectiveness to a continuum from negative (ineffective) to positive (effective) valence (e.g., Simon et al, 2022; van Knippenberg & van Knippenberg, 2005). A pre-trained sentiment analysis model from the Python library Transformers (Wolf et al, 2020) was used to score each leader’s results narrative on positivity and negativity.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Examining the heldout likelihood (the predictive strength of each model on a heldout data set) along with semantic coherence (the average interpretability of topics) suggested that the best fitting models contained five to seven topics. We used the visualization tool LDAvis (Sievert & Shirley, 2015), adapted to view structural topic model results (Roberts et al, 2019), to visualize the topics in terms of their overlap, coverage of the narrative space, and top words. Conceptually, a model of six topics best fit the situational narratives.…”
Section: Analyze Structural Leadership Situation Cuesmentioning
confidence: 99%